1997
DOI: 10.1002/(sici)1098-1063(1997)7:2<184::aid-hipo5>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal protein malnutrition on mossy fibers of the hippocampal formation in rats of four age groups

Abstract: The present study was undertaken to investigate the effect of prenatal protein deprivation on the postnatal development of the mossy fiber plexus of the hippocampal formation on postnatal (P) days 15, 30, 90, and 220. Although there is extensive information about the effects of malnutrition on cell body and dendrite morphology, little attention has been paid to axons or axon plexuses. The mossy fiber plexus represents the dentate gyrus granule cell axonal projection to areas CA4 and CA3 of the hippocampal form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
2
13
0
3
Order By: Relevance
“…The structural and functional development of hippocampus is susceptible to prenatal or perinatal nutrition (Cintra et al, 1997;Morgane et al, 2002) or stress. Different strains of mice from different rearing condition and domestication background demonstrated differences in hippocampal development (Schaefers, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional development of hippocampus is susceptible to prenatal or perinatal nutrition (Cintra et al, 1997;Morgane et al, 2002) or stress. Different strains of mice from different rearing condition and domestication background demonstrated differences in hippocampal development (Schaefers, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies by the Morgane and Galler group had shown that malnutrition induces alterations in the synaptic microarchitecture of the hippocampal circuit that is responsible for theta generation. [15][16][17] Since theta activity represents the output of the hippocampal system and thus reflects its integrity, 18 theta activity in wakefulness and for NREM and REM sleep was analyzed to document any malnutritioninduced alterations. The results obtained indicated that the theta frequency peak during wakefulness was lower in both the chronic and prenatally malnourished groups.…”
mentioning
confidence: 99%
“…A literatura tem mostrado que a desnutrição pode provocar alterações no sistema nervoso central (Santucci et al, 1994;Cintra et al, 1997;Almeida et al, 1996;Morgane et al, 2002). O presente estudo mostrou que ratos submetidos à desnutrição protéica apresentaram um maior percentual de entradas e de tempo de permanência nos braços abertos do labirinto em cruz elevado (LCE), quando comparados a animais que não foram submetidos à restrição de proteína.…”
Section: Labirinto Em Cruz Elevadounclassified
“…Em ratos, o déficit na ingestão de proteína durante o período de gestação pode resultar em atrasos no desenvolvimento físico e cerebral. (Santucci et al, 1994;Cintra et al, 1997;Almeida et al 1996;Morgane et al 2002). Na desnutrição podem ser observadas alterações bioquímicas e neurológicas (Hermel et al, 2001;Feoli et al, 2006), resultando também em alterações comportamentais (de Oliveira, 1985;Riul et al, 1999) e atrasos em funções intelectuais e cognitivas (Barnes, 1976;Brozek, 1979, 1983, Wainwright e Colombo, 2006.…”
Section: Introductionunclassified
See 1 more Smart Citation